PENGARUH LINGKUNGAN KERJA DAN INSENTIF TERHADAP KEPUASAN KERJA (STUDI PADA PETUGAS LABORATORIUM PUSKESMAS DI KABUPATEN LOMBOK BARAT ) - lalu samsu rizali (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at determining the effect of work environment and incentives on the work satisfaction of health center laboratory workers in West Lombok. The population of this research are all 40 workers of health center laboratory in West Lombok. The analysis is completed with multiple linear regression. The research showed that work environment and incentive simultaneously have positive and significant  effect on the work satisfaction. Partially, work environment has positive a significant  effect on work satisfaction and incentive  has positive and significant effect on work satisfaction. Work environment has more dominant  effect comparing to the incentive effect on the work satisfaction of workers of health center laboratory in West Lombok.Keywords :  Work Satisfaction, Work Environment, Incentive.